2015
DOI: 10.3389/fgene.2015.00107
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing neutral genomic diversity and selection signatures in indigenous populations of Moroccan goats (Capra hircus) using WGS data

Abstract: Since the time of their domestication, goats (Capra hircus) have evolved in a large variety of locally adapted populations in response to different human and environmental pressures. In the present era, many indigenous populations are threatened with extinction due to their substitution by cosmopolitan breeds, while they might represent highly valuable genomic resources. It is thus crucial to characterize the neutral and adaptive genetic diversity of indigenous populations. A fine characterization of whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 83 publications
(106 reference statements)
9
77
0
2
Order By: Relevance
“…These findings are very similar to those examining other Moroccan goat populations, i.e., Black, Draa and Northern (Benjelloun et al, 2015), for which three principal components explained only 5.8% of the variance among the three populations. Hilal et al (2016) reported weak differentiation in the Hamra goat population in two different locations of Morocco.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These findings are very similar to those examining other Moroccan goat populations, i.e., Black, Draa and Northern (Benjelloun et al, 2015), for which three principal components explained only 5.8% of the variance among the three populations. Hilal et al (2016) reported weak differentiation in the Hamra goat population in two different locations of Morocco.…”
Section: Discussionsupporting
confidence: 86%
“…Genetic differentiation (FST) among the populations was not detected (2%), and 98% of the genetic variability of the studied subpopulations was due to differences among individuals of the total population and not to differences among the geographical subpopulations. Our FST values are notably inferior to those reported by Ouragh et al (2012) but are similar to those obtained with SNPs for other Moroccan goats (Black of the Atlas, Draa and Northern populations) by Benjelloun et al (2015).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The genome of goats, which have diverse production potentials and extensive adaptation to diverse environments, provides a unique opportunity for identifying signatures associated with selection. Array- or sequencing-based detection of signatures during the selection process has been described in cattle456, chicken7, pigs8910, sheep1112, and recently in goats131415. By using whole-genome resequencing (WGS) data, Benjelloun et al .…”
mentioning
confidence: 99%
“…But the morphologicaland behavioral characteristics of modern domestic goats have greatly changed compared with wild progenitor, the Bezoar goat ( Capra aegagrus )2. Compared with the Bezoar goat, modern goats exhibit a reduction in body size, a more docile demeanor, a series of coat color variants and the ability to adapt after domestication and breed formation, which have left detectable signatures of selection within the genomes34. Hence, scanning of selection signature can’t only provide straightforward insights into the mechanism of evolution events but also use for identifying functional genes of important economic traits or causative variations of phenotypic diversity.…”
mentioning
confidence: 99%